(untitled) (AYUSHDHARA, 2022)
Does Universe has a creator? There are two schools of thought, yes (Aastik), no (Nastik). This Aastik and Nastik form a view point called Darshan (philosophy). Aastik Darshan Shastra (6) are a key to creation of universe by creator. Learning about the creator and its properties-Guna lead to the development of the universe. Each Darshan had different way of looking resulting into diversity of thought as well as confusion. Yog professes only one Guna. Sankhya says 3 (Sat, Raj and Tam), Vaisheshik says 24 Guna and Nyaaya says 16 Guna, Mimansa is application of Guna (development of subjects like Ayurveda, Dhanurveda, Gandharvaveda and Arthashastra) and Vedant says everything is a Guna. Sankhya Darshan professes how many are holding the universe and its reasons of approach - Why? This gives the theory of Sat being causal body or Kaaran Sharir, Raj being Sukshma Sharir or subtle body and Tam being Sthool Sharir or gross body and each body is with 5 elements as स(ष) त म र ज. These three Guna of divine were often misunderstood or misinterpreted. One area of the application of Darshan leads to the development of Ayurveda. A logical structure is presented in the form of 3 Sharir represented by Sat, Raj and Tam professed by Sankhya Darshan and its application to Ayurveda. The study endeavours at the application of Sankhya yog on Ayurveda and opens the doors for further study in relation to Dhanurveda, Gandharvaveda and Arthashastra.